Modelling and analysis of energy absorption capacity of 3D printed structure design (A) - Yen, Wei Shing (Nanyang Technological University, 2022)
Lightweight structures are crucial in multiple industries but studies on novel structures have been decreasing in recent years. Hence, the objective of the study was to model and conduct an initial analysis of the deformation, stress, and energy behaviour of the given novel design so as to create a new possibility to improve current engineering structures. In the present study, the given novel design is proposed by combining Kirigami technique and Auxetic movements. The given design was then modelled in SOLIDWORKS and numerically simulated in ANSYS EXPLICIT DYNAMICS to provide in-depth analysis for compression and impact loading for two orientations: horizontal and vertical. The results from compression loading analysis show that the horizontal oriented model is capable of maintaining its auxetic performance with longer densification time. Meanwhile, under higher compression displacement, the vertical oriented model’s auxetic performance is restricted by its geometry. Results from impact loading shows that the horizontal oriented model has better energy absorption and dissipation capabilities compared to the vertical oriented model due to its deformation behaviour when impacted. The results from this study could provide a new concept for the design and optimisation of lightweight energy absorption structures.